Rhizobium Inoculation and Chemical Fertilisation Improve Faba Bean Yield and Yield Components in Northwestern Ethiopia - Getenesh Genetu; Markku Yli-Halla; Mekonnen Asrat; Mihiret Alemayehu (Agriculture, 2021)
The productivity of the faba bean has declined in Ethiopia, owing to poor management practices, such as blanket fertilisation. In 2018, a field experiment was conducted in a Nitisol soil during the main cropping season in Northwestern Ethiopia, to determine the amount of chemical fertiliser and Rhizobium inoculant to be used for the optimum yield within economic feasibility. The experiment consisted of a factorial combination of five rates of blended NPSZnB fertiliser (0, 60, 121, 180 and 240 kg ha−1) and three rates of inoculant (0, 500 and 750 g ha−1). Sole chemical fertilisation, as well as inoculation, individually produced a seed yield of 2.3–2.5 t ha−1, about 1.0–1.2 t ha−1 more than the control. However, the maximum seed yield (3.3 t ha−1) was recorded from the combined application of both the chemical fertiliser and the inoculant. The seed yield correlated closely with the number of active nodules (R2 = 0.78 **), suggesting a substantial contribution of symbiotic N2 fixation. Inoculation increased the N content of the seed yield by at least 30 kg ha−1. Chemical fertilisation, containing at least 44 kg ha−1 of mineral N does not appear to have an adverse effect on N2 fixation. The combined use of 180 kg ha−1 blended fertiliser with 750 g ha−1 inoculant, producing a maximum net profit of 72,918 birr ha−1 (EUR 2232), is recommended for the study area. This study emphasises that (1) inoculation alone can produce as much seed as the maximum rate of chemical fertilisation, but (2) the maximum yield was produced with a combined use of inoculant and chemical fertiliser, by promoting the vigour of the nodules and N2 fixation.